Implementación de algoritmos de control sobre una microrred fotovoltaica para carga de vehículos eléctricos (2021)
This thesis focuses on the creation of a photovoltaic microgrid in order to charge electric vehicles. The methodology was based on the sizing of the number of solar panels required for the operation of the system, as well as the batteries required to supply the load. In addition, DC-DC, DC-AC converters with their respective drivers are designed. Finally, a supervisor is programmed for decision-making depending on the environmental conditions.